2012
DOI: 10.3928/01484834-20120823-01
|View full text |Cite
|
Sign up to set email alerts
|

Videoconferencing Expands Nursing Students’ Cultural Realm

Abstract: Nurse educators struggle to provide culturally diverse community health clinical placements that cultivate cultural awareness, knowledge, and competence among baccalaureate nursing students. Public health nurses observe that many new nursing graduates lack the fundamental knowledge, skills, and affective behaviors necessary to work with culturally diverse populations. To address this, nursing faculty from two schools partnered to strategize, design, implement, and evaluate a community health assessment project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…El estilo de aprendizaje se piensa que puede tener influencia en el compromiso de los estudiantes con sus estudios, de forma que aquellos métodos docentes que hacen que el estudiante busque activamente el conocimiento son proclives a conseguir un estudiante con mayor compromiso que aquellos otros estilos más tradicionales en que los estudiantes tienen un papel más pasivo (12)(13)(14)(15)(16)(17)(18)(19) .…”
Section: Enfermería Globalunclassified
“…El estilo de aprendizaje se piensa que puede tener influencia en el compromiso de los estudiantes con sus estudios, de forma que aquellos métodos docentes que hacen que el estudiante busque activamente el conocimiento son proclives a conseguir un estudiante con mayor compromiso que aquellos otros estilos más tradicionales en que los estudiantes tienen un papel más pasivo (12)(13)(14)(15)(16)(17)(18)(19) .…”
Section: Enfermería Globalunclassified
“…In this project, students' dialogue related to indigenous populations, poverty, communicable disease and global health threats may reinforce learning related to public health nursing principles including the need for respect and appreciation for other cultures. This knowledge addresses the concerns raised by Pirkey et al, [20] and also encompasses the QUAD Council competencies for public health nurses. [21] The American Nurses Association Scope and Standards of Public Health Nursing [22] and the cultural competency behaviors identified by the American Association of Colleges of Nursing.…”
Section: Discussionmentioning
confidence: 99%
“…Pirkey, Levey, Newberry, Guthman and Hansen [20] identified that public health nurses are concerned about new graduate nurses' competence for working with diverse populations. The students' interchanges using video conferencing provided an ideal context to consolidate core public health concepts taught in their respective classes.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 However, no previous Japanese study clarifies the educational methods of health counselling considered within its own culture The conspicuous features of Japanese culturally appropriate health counselling methods were clarified in this study so as to make future use of these methods more efficient. This aim of public health nursing must influence health counselling methods; therefore, the PHNs must consider values or relationships common to community residents.…”
Section: Discussionmentioning
confidence: 99%